Membangun Model Pengelolaan Sumberdaya Perikanan Berkelanjutan Berdasarkan Karakteristik Sosial Ekonomi Masyarakat Nelayan Tinjauan Sosiologi Antropologi - Moch Prihatna Sobari; Rillus A Kinseng; Fatriyandi N Priyatna (Buletin Ekonomi Perikanan, 2003)
Indonesia entities of very abundant sea and coastal resources. The resources need to be managed well in order to prevent any destruction that can lead to decrease human quality life. This research aims at developing a model of fisheries resources management in Karang Jaladri village of Ciamis Regency. The model Is based on the characteristics of fishermen socio-economics. Socio-antrophology approach is used to explain the findings. The research outcomes Is that local knowledge can facilitate the resources management. Co-management can be used as an alternative approach In Implementing sea and coastalresources management.